Navigating the WTO's Working Group on Trade and Transfer of Technology: A critical analysis from the perspective of developing countries - Nirmalya Syam (South Centre, 2024)
This paper critically analyzes the operations and effectiveness of the World Trade Organization's (WTO) Working Group on Trade and Transfer of Technology (WGTTT). Despite the establishment of the WGTTT in 2001 with a mandate to enhance technology flows to developing countries, the Group has struggled to produce meaningful outcomes due to divergent priorities between developed and developing countries. This paper finds that the WGTTT remains an exploratory discussion forum rather than a negotiation platform with the capacity to generate new initiatives that address the technology transfer needs of developing countries. Key reforms are proposed, including transitioning to a negotiation-oriented approach, improving the balance of member priorities, and focusing on actionable themes to enhance the WGTTT effectiveness in fostering technology transfer to developing countries.
Keywords: 300; Doha Development Agenda; Innovation; Intellectual Property; Nirmalya Syam; Technology; Technology Transfer; Trade; TRIPS; TRIPS Agreement; World Trade Organization (WTO); WTO Working Group on Trade and Transfer of Technology (WGTTT)